Phytochemical Composition and Antibacterial Activity of Trachyspermum copticum L. essential oil, East Azerbaijan, Iran - Haedeh Mobaiyen; Maisam Nasarollah Pour; Franak Elmi (Pasteur Institute of Iran, 2015)
Introduction: The aim of this study was to characterize the chemical composition and antimicrobial activity of Trachyspermum copticum essential oil (EO). Methods: The chemical composition of seed samples obtained from Mianeh city in East Azerbaijan, was assessed using gas chromatography-mass spectrometry (GC-MS). The antimicrobial activity was evaluated by disc diffusion method against methicillin-resistant Staphylococcus aureus (MRSA), other extended-spectrum beta-lactamases (ESBLs) producing, as well as Gram-negative and Gram-positive bacteria. The minimum inhibitory concentration (MIC) value of EO was assessed using agar dilution method. Results: Thirteen monoterpene hydrocarbons (57.6%) and oxygenated monoterpenes (42.4%) compounds were identified in the EO, of which, 3 compounds, including thymol, m-cymene, and, γ-terpinene were the major components of the EO with quantities of 41.9, 33.53, and 20.42%, respectively. The EO showed antimicrobial activity against ten microorganisms, especially Streptococcus sanguis, S. aureus (MRSA strain), and Klebsiella pneumoniae (ESBL-producing strain), which was potentially better than tetracycline and kanamycin. Conclusion: This study confirmed that EO of T. copticum has in vitro antimicrobial activity against Gram-negative and Gram-positive bacteria, which has made it an alternative antibacterial agent.